(untitled) (Global Journal of Science Frontier Research, 2016)
Three selected sites with gradual distances from Al-Daura thermal power station (0.5 km (St. 1), 1Km (St. 2) and 2Km (St.3), were chosen for sampling according to the direction of downwind of site. In addition, one of unpolluted site was chosen for comparison as a control site in Baghdad around 4 Km upwind from Al-Daura thermal power station. The samples were taken for two seasons; the first season was in December 2014 and the second season was in March 2015. The concentrations of some pollutants that originated from Al-Daura thermal power station as air pollutants and heavy metals in the soil were measured. Whereas the results of heavy metals in soil refer to significant differences in the concentrations of Nickel (Ni), Cadmium (Cd), and Copper (Cu) in all three sites comparing with control site, they were higher in site 2 than other sites, while the Lead (Pb) concentration was higher in site 3. There was a significant increase in concentrations of Ni and Pb in the first season than in the second season, whereas no significant differences appeared in the concentrations of Cd and Cu between the two seasons.